Proses Penyelesaian Kekerasan Seksual Terhadap Anak Melalui Proses Peradilan Pidana (Studi Kasus Tentang Penyidikan Di Polresta Surakarta) - Wijaya, Resza Danang, Kuswardani, S.H., M.Hum (2017)
This study aims to determine the process of settlement of sexual abuse of children at the level of the investigator and to determine the barriers experienced investigators during the investigation takes place. The method used is empirical normative and descriptive research. The data source consists of primary data, interviews and secondary data is data of primary law. Methods of data collection done by field data synchronizes with legal regulations in force then analyzed qualitatively. The results showed that the process of settlement of sexual abuse of children is in conformity with the legislation in force, although there are tips and tricks certain not contained in the laws and legislation that used investigator